Analisis Implementasi Maqashid Syariah pada Rumah Sakit Berkompetensi Syariah di Indonesia Sebagai Unique Value Preposition - Yuhanah, Siti; Muhajirin, Muhajirin; KH, Hasbi Abdul Al-Wahhab (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This article explain the implementation of maqashid syariah in sharia-competent hospitals in Indonesia. The analysis of the fulfillment of maqashid sharia in sharia hospital services aims to display a unique value preposition to take a niche in the healthcare market. Maqashid Syariah was chosen because Islamic values in sharia hospital services are a critical factor which is one of the considerations for consumers in choosing health services. This research uses the library research method by conducting a review of books, journals, articles, and various other references related to sharia maqashid then the researcher processes the data by analyzing its application to sharia hospital services. The results showed that sharia-competent hospitals have implemented the fulfillment of sharia maqashid in their service quality standards, namely religious protection (hifdz ad-din), life protection (hifdz an-nafs), protection of offspring (hifdz an-nasl), protection of reason (hifdz al-aql), and protection of property (hifdz al-mal). Keywords: Maqashid Syariah; Sharia Hospital; Islamic Service Quality Dimensions; Unique Value Prepositions